A review of recent developments in geopolymer concrete - Chithambar Ganesh, A.; M. Muthukannan, Dr. (International Journal of Engineering and Technology, 2018)
Geopolymer concrete is proved to have high strength, lesser shrinkage, resistance against reinforcement corrosion, acid and sulphate resistance, freeze-thaw resistance, fire resistance and resistance to alkali-aggregate reaction. There are many parameters which influence the strength characteristics of Geopolymer Concrete. They are types and fineness of Source alumino silicate material used, concentration and type of alkaline activators used, curing temperature and curing time, utilization of M-sand etc. High performance characteristics could be achieved through the correct choice of these parameters. This review paper focuses on the influence of different variables on the properties of geopolymer concrete and the progress in the field of geopolymer concrete. Consequently many research papers pertaining to the geopolymer have been reviewed in this state of art paper.Â Â